Anesthetic effects of a mixture of xylazine, ketamine, and buprenorphine in laboratory rats subjected to short surgical procedures - Luca Pennasilico; Federica Serino; Margherita Galosi; Angela Palumbo Piccionello; Alessio Angorini; Fabrizio Dini; Caterina Di Bella (Open Veterinary Journal)
Background: Rodents are commonly used as models in experimental procedures, and researchers often need to perform rapid manipulations involving sedation and analgesia.